Effect of methodology and sampling time on the taxa richness of aquatic macroinvertebrates and subsequent changes in the water quality index from three tropical rivers, Costa Rica - Maue, Thomas (2008)
Aquatic macroinvertebrates have proven to be a useful tool for water quality studies and biomonitoring in temperate areas. Recently, efforts have been made to adapt these methods to tropical environments, but there are still uncertainties concerning the most adequate methodology and collecting time. Three rivers, one in Alajuela province and two in Puntarenas province in Costa Rica, were tested with two methods and different collecting times, in the rainy and dry season. The first method involved collecting of organic and inorganic material for a fixed time period (3, 5, 8, 10 min) with a strainer. This material was transferred to a plastic bowl containing 70% alcohol and aquatic macroinvertebrates were sorted out in the laboratory. With the second method the specimens were collected in the field directly out of the strainer for a total collecting time of 120 minutes and preserved immediately with 70% alcohol. In order to obtain species accumulation curves for this method, subsamples were taken every 15 minutes. The data analysis showed that the abundance and taxa richness was higher with the second method, and a higher number of genera could be found with increasing collecting time, but not necessarily a higher number of individuals. A difference in the number of individuals between rainy and dry season was observed. Species accumulation curves for samples taken with both methods showed that new genera and families were still being found after the maximum time of collection, no matter which season or river. Categories of water quality obtained from the BMWP-CR index varied greatly among sampling times and methods used. The second method always achieved a higher water quality than the longest sampling time (10 min) in the first method. However, it still didn’t reach the level obtained for all families found in both methods combined. Although the first method is the one officially used in most sampling protocols for biomonitoring in temperate zones, these results suggest that more extensive testing of adequate sampling time and methodology is still necessary for tropical rivers. Rev. Biol. Trop. 56 (Suppl. 4): 257-271. Epub 2009 June 30.